THE EFFECT OF PRODUCT QUALITY, PRICE, AND PROMOTION ON CAR PURCHASING DECISIONS HONDA BR-V (CASE STUDY OF HONDA BR-V SALES AT HONDA DEALERS BANDUNG) - RIZWAN, Tazkia Anindita; RIZWAN, Desty Fauziah Ramadhani; RIZWAN, Rizky Aulia Rachman; RIZWAN, Indira Putri; RIZWAN, Mariana Rachmawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Research on the purchasing decisions of consumers to a product car is already pretty much done. This study aims to examine the factors that influence consumer purchase decisions on products of BR-V Honda car. The factors used are product, price, and promotion as part of a marketing strategy in the hypothesized influence on purchase decisions of BR-V Honda cars. This study used a sample of 200 respondents who are Honda Bandung City customers by providing a questionnaire with 45 questions, which include variable product quality, pricing, and promotions on consumer purchasing decisions. Data analysis tool used is multiple regression with the help of statistical program SPSS for windows version 23. The hypothesis test obtained t value for the quality of the product (X1) of 3.031 with a significance level of 0.003, variable prices (X2) t count equal to 5.820 with a significance level of 0.000 and t variables sale (X3) of 3.091 with a significance level of 0.002, Thus, it means the results of the t test analysis expressed significant results for all variables and hypotheses accepted. The results of multiple regression analysis also showed the value of determination coefficient of 0.557 which means that the variable quality of the product, price and promotional influence purchasing decisions by 55.7%, while 43.3% is influenced by other variables that are not observed in this study.